АНАЛІЗ НАЛАШТУВАННЯ ПРИСТРОЇВ АВТОМАТИЧНОГО ЧАСТОТНОГО РОЗВАНТАЖЕННЯ З УРАХУВАННЯМ ЄВРОПЕЙСЬКИХ ВИМОГ - Стелюк, А.О.; Лук’яненко , Л.М. (Інститут електродинаміки НАН України, Київ, 2024)
The paper deals with the structure of under-frequency load shedding (UFLS) relays in the interconnected power system (IPS) of Ukraine. The equivalent power system model to study the UFLS operation is developed, and UFLS configuration scenarios considering the requirements of ENTSO-E, are configured. The frequency stability for different scenarios of UFLS settings considering planned and emergency active power imbalances are studied. The plots illustrating the frequency change in the power system under these conditions are presented. References 4, table 1, figures 5.